“De Tjolomadoe”: from Cultural Heritage to Industry 4.0 - Yuke Ardhiati; Setia Damayanti; Diptya Anggita; Adryanto Ibnu Wibisono; Ramadhani Isna; Ade A.S. Fajarwati; Amurwani Dwi Lestariningsih (Journal of Applied Sciences and Advanced Technology, 2020)
This article describes a combining research innovation (in cultural heritage) with Industry 4.0 at “De Tjolomadoe” the used sugar factory building. The original name is Suikerfabriek Tjolomadoe at Malangjiwan Karang Anyar. Owned by Kanjeng Adipati Mangkunegara IV of Surakarta built in 1861. By fact, it is the only one sugar factory owned by the Javanese Royal Family during Dutch Colonial era. After Republic of Indonesia was built, it nationalized by Indonesian Government (1946) during Soekarno era (1945-1967). After held it in Adaptive Reuse in 2017 the building’s roles a new function as Convention and Heritage. By refers to a qualitative research, the study aims to finding the elements of industrial 4.0 SDGs in “De Tjolomadoe” included the museum concept. Inside the Convention and Heritage building was found an edutainment facility to accommodate the millennial age. Behind, the gigantic of sugar factory machines, dioramas, archives, miniatur models, original drawings are shows as museum collections. In the huge of “De Tjolomadoe” outdoor lanscape there are the originally of building construction by giant typo”ANNO 1928 ” in the brick wall, the Art Deco style of the Resident’s House Administrator, the Prince’s Gazebo, the Sarkara Hall as a multi-function hall, and prefecly by the beautiful Sunken Plaza. Related to industrial 4.0 SDGs they show the internet of thing (IoT) by created the Old Javanese civilization of sugar factory. Especially in The Royal Landscape’s corner there are “glow in the dark” by an artificial intelligent architecture. It shows the glory of the last Sugar Factory in Java Island during at the Colonial Era. Now, by the successfully of the Adaptive Reuse in 2017 was composed The Cultural Heritage with industry 4.0 has modified “De Tjolomadoe” to be one of the venue of the millennial visitors to create their happy times during its appreciation.